Coingestion of carbohydrate-protein during endurance exercise: Influence on performance and recovery - Saunders, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
Endurance athletes commonly consume carbohydrate-electrolyte sports beverages during prolonged events. The benefits of this strategy are numerous—sportsbeverage consumption during exercise can delay dehydration, maintain blood glucose levels, and potentially attenuate muscle glycogen depletion and central fatigue. Thus, it is generally agreed that carbohydrate-electrolyte beverages can improve endurance performance. A controversy has recently emerged regarding the potential role of protein in sports beverages. At least 3 recent studies have reported that carbohydrate-protein ingestion improves endurance performance to a greater extent than carbohydrate alone. In addition, carbohydrate-protein ingestion has been associated with reductions in markers of muscle damage and improved postexercise recovery.Although many of these muscle damage and recovery studies examined postexercise nutritional intake, recent evidence suggests that these benefits may be elicited with carbohydrate-protein consumption during exercise. These findings are intriguing and suggest that the importance of protein for endurance athletes has been underappreciated. However, 2 studies recently reported no differences in endurance performance between carbohydrate and carbohydrate-protein beverages. The varied outcomes may have been influenced by a number of methodological differences, including the amounts and types of carbohydrate or protein in the beverages, the exercise protocols, and the relative statistical power of the studies. In addition, although there are plausible mechanisms that could explain the ergogenic effects of carbohydrate-protein beverages, they remain relatively untested. This review examines the existing research regarding the efficacy of carbohydrate-protein consumption during endurance exercise. Limitations of the existing research are addressed, as well as potential areas for future study.